A SPATIOTEMPORAL MODEL WITH OPTIMAL CONTROL FOR THE NOVEL CORONAVIRUS EPIDEMIC IN WUHAN, CHINA. (2021) - KOURRAD, AHMED; ALABKARI, AMINE; ADNAOUI, KHALID; ZAKARY, OMAR; TABIT, YOUSSEF; LAAROUSSI, ADIL EL ALAMI; LAHMIDI, FOUAD
No abstract available